An approach to the investigation of optimal quadrature formulas for singular integrals with fixed singularity - Shabozov, M. Sh. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
For classes of functions given on the segment [0,1], we obtain optimal quadrature formulas for singular integrals with fixed singularity. The obtained results are extended to the case of two-dimensional integrals.